Karakteristik fisik roti yang memanfaatkan ubi ungu (Ipomoea Batatas Var Ayamurasaki) dan ubi Cilembu (Ipomoea batatas L.): Physical characteristic of bread using purple sweet potato (Ipomoea Batatas var Ayamurasaki) and Cilembu sweet potato (Ipomoea batatas L.) - Rahardjo, Monika; Sihombing, Monang (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Purple sweet potato and Cilembu sweet potato offer unique advantages when added to bread dough formulations. Purple sweet potato, known for its rich nutritional profile and vibrant colour, while Cilembu sweet potato is known for its sweetness. Both purple sweet potato and Cilembu sweet potato offer opportunities to diversify bread formulations, especially with a number of health benefits on offer. By utilizing these two sweet potatoes by adding them to a previously researched sourdough bread dough, this study aimed to examine the physical characteristics of the final sourdough bread. The research method consisted of selecting and processing sweet potatoes for bread formulation, making sweet potato sourdough bread, physical analysis namely colour and texture and statistical analysis. The results showed that the addition of sweet potato, both purple and Cilembu, caused significant differences in all colour parameters, namely parameters L, a and b of the bread. In texture characteristics, the addition of Cilembu sweet potato caused significant differences in stiffness parameters while purple sweet potato caused significant differences in hardness, springiness and springiness index parameters. The addition of purple sweet potato and Cilembu yam to white bread affects the physical characteristics especially in colour and texture.